UPAYA MENINGKATKAN KEMAMPUAN KEAKSARAAN AWAL MELALUI PENGGUNAAN MEDIA KOTAK PINTAR PADA KELOMPOK A DI TKQ AN NAMLU KARAWANG - Wijayanti, Lutfi Asih; Syafrida, Rina; Aisyah, Dewi Siti (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The aim of this research is to explain the learning process and outcomes at TKQ An Namlu Karawang through activities using smart box media to improve early literacy skills. This research uses classroom action research with the Kemmis and McTaggart model which includes action, planning, observation and reflection. This research consisted of two cycles with cycle I having six meetings and cycle II having four meetings. In these two cycles, data analysis was carried out using qualitative and quantitative techniques. Qualitative data analysis was carried out by looking at data from observation notes, interview notes and documentation notes. Quantitative data analysis was carried out through descriptive statistics by comparing the results obtained from pre-action, cycle I and cycle II. The results of this research show an increase in initial literacy skills as evidenced by the data obtained during pre-action, the percentage reached 42%, and increased by 25% so that in cycle I the percentage obtained was 67%, and in cycle II it increased again by 26% with results by 93%.